Irrigation scheduling for Humulus lupulus (L.) cv. 'Nugget': climate and soil-plant relations - Fandiño, María; Martínez, Emma María; Rey, Benjamín Jesús; Valladares, Juan; Olmedo-Nadal, José Luis; Mirás-Avalos, José Manuel; Cancela, Javier José (BrewingScience, 2019)
Hop (Humulus lupulus L.) yield depends greatly on weather conditions, particularly on rainfall, thus varying from year to year. In this sense, irrigation management is an essential tool for maintaining hop yields at an adequate level. However, hop water demands must be accurately estimated in order to develop an efficient irrigation strategy. The current study was performed over three years (2012–2014) in a 5-year old hop yard located in NW Spain. The hop yard was divided into two plots: in 2012, plot 1 was rain-fed and plot 2 was irrigated, whereas in 2013 and 2014 both plots were irrigated but to different water amounts. This work estimates the water status of hop cv. "Nugget" (2012–14) using leaf water stress indicators (LWSI) (relative water content and leaf water potential) and their relationships with soil water content (SWC). Moreover, a set of single crop coefficients (Kc) for the different phenological stages of the growing season has been developed for hop, under the common management conditions in Galicia (NW Spain). Soil water content at 80 cm depth was measured on 12 points per plot. Midday leaf water potential (Ψm), osmotic potential (Ψo), turgor pressure (Ψp) and relative water content (RWC) of the leaves were determined weekly from June to September on six plants per plot. Single Kc were estimated employing a soil water balance approach using previous data. Significant differences in SWC were detected between plots, especially by the end of the growing season. In 2013 and 2014, Ψm and Ψo were slightly more negative in plot 2 than in plot 1, 6 % and 2.5 %, respectively. Significant differences between plots were detected for Ψp and RWC in 2014, with plants in plot 1 showing the highest values for these LWSI. Using data from two seasons, significant coefficients of determination were observed for Ψp vs. SWC (R2=0.42), Ψp vs. RWC (R2=0.41) and Ψo vs. Ψm (R2=0.98). The Kc values obtained for an average year were 0.69, 1.02 and 0.84 for the initial, mid-season and end stages of the hop-growing season. These results will enable hop growers in Galicia to manage irrigation more efficiently.